One-pot synthesis of iron oxide nanoparticles: effect of stirring rate and reaction time on its physical characteristics - Idris, Auni Hamimi; Che Abdullah, Che Azurahanim; Yusof, Nor Azah; Abdul Rahman, Mohd Basyaruddin (Taylor & Francis, 2022)
Iron oxide nanoparticles (IONP) have tremendous potential in various applications due to their unique physical and magnetic properties. Controlling synthesis parameters is essential to obtain IONP with desired properties. The influence of stirring rate and reaction time during synthesis of IONP from thermal decomposition of FeOOH on the particle size, crystallinity, and magnetic properties of the IONP were investigated. IONP produced at different reaction times and stirring rates had similar spherical shapes with low polydispersity. Particle size was found to increase from 4.9 nm to 8.6 nm when reaction time increased from 15 to 60 min, with the highest saturation magnetization of 34.3 Am2/kg obtained at 60 min. Stirring rates of 400 and 500 rpm produced IONP with better crystallinity and saturation magnetization than 300 and 600 rpm. The properties of IONP can be tuned by selecting appropriate stirring rates and reaction times during synthesis to suit the intended applications.